Approaches for the Racial and Ethnic Determination of a Person - Mahmudova, Shafagat Jabrail (European Journal of Applied Sciences, 2015)
The article describes the approaches for the racial and ethnic determination of a person. Ethnic belonging of any person is one of his groups of signs; hence, the need for its study may be due to a variety of reasons, such as the recognition of a person’s face, creating identification card, making up the image of an unknown person, or of a missing person or suspected criminals, and so on.